The Importance of Both Brand Satisfaction and Brand Attitude toward Brand Loyalty: A Comparative Study within The Indonesian Aviation Sector - Nicholas Wilson; Marcellino Jason Ferdinand Sugiyanto (Jurnal Manajemen Bisnis dan Kewirausahaan, 2021)
This study was conducted in order to determine the effect that both brand satisfaction and brand attitude had toward brand loyalty in the Indonesian aviation sector. This study implements a comparative study method, in which data which were gathered from two cities which are located within the same countries were assessed separately and compared to each other. This study implements survey method with all of the data from the respondents will be gathered and collected using the questionnaires. A total of 300 respondents participated in this study, which are comprising of 150 respondents from Jakarta and 150 respondents from Surabaya. All of the data gathered from each city will be analyzed individually, in which later on the results of both cities will be compared to each other in order to gain a better understanding regarding the relationships between variables in each city. All of the data which had been collected from the respondents will be assessed using PLS-SEM method. After analyzing all of the data, authors conclude that both brand satisfaction and brand attitude positively affecting brand loyalty within the Indonesian aviation sector in both cities, which are Jakarta and Surabaya. The results obtained in this study highlight the importance of airlines companies conducting their business in the Indonesian aviation sector to keep enhancing consumers’ satisfaction and positive attitude toward the brand, in which when consumers’ satisfaction and positive attitude toward the brand will eventually evolve into loyalty which could increase the airline’s competitiveness level compared to the other competitors. Penelitian ini dilakukan guna mengetahui bagaimana peranan brand satisfaction serta brand attitude di dalam mempengaruhi brand loyalty konsumen pada sektor penerbangan di Indonesia. Penelitian ini mengimplementasikan metode studi komparasi, dimana data pada penelitian ini akan dikumpulkan dari responden yang berasal dari dua kota yang berbeda di dalam negara yang sama, yang dimana nantinya masing-masing data dari setiap kota akan dianalisis dan dibandingkan 1 dengan yang lainnya guna mengetahui secara menyeluruh bagaimana hubungan antar variabel yang diteliti pada studi ini. Penelitian ini berbentuk survei, yang dimana kuesioner digunakan sebagai alat untuk mengumpulkan seluruh data yang dibutuhkan dari responden. Sebanyak 300 responden berpartisipasi pada studi ini, yang dimana masing-masing sebanyak 150 responden berdomisili di Jakarta, serta sebanyak 150 responden lainnya berdomisili di Surabaya. Seluruh data yang telah dikumpulkan kemudian dianalisis dengan menggunakan metode PLS-SEM. Berdasarkan hasil analisis data, peneliti dapat menyimpulkan bahwa brand satisfaction serta brand attitude berpengaruh positif terhadap brand loyalty.